Influence of media, nitrogen, indigenous microorganism and water stress on bioactive compounds and biomass yield of Andrographis paniculata (Burm.f.) wall. ex nees - Salih Ali, Shara (2014)
The current interest in reducing the herbal product importation by cultivating medicinal plants as Hempedu bumi, may have great impact on increasing the production of herbs in the local herbal industry. Growing plants under soilless media enable year round production of Hempedu bumi biomass. Although, some of soilless media (SM) components are cost effective and finding an alternative which is cheap and available locally in combination with indigenous microorganism might reduce applied rate of N chemical fertilizer. Besides the fact that organic and microbial amend d technique can enhance the growth of healthy herb, but also there is a need to increase the secondary metabolites in the pharmaceutical herb industry and this could be achieved by undergoing the plant through water stressed condition. A preliminary study was carried out to determine the physical, chemical and microbiological properties of the soilless media that has used in the study which where; (coconut coir dust (CCD), empty fruit bunch compost (EFBC) and peat. Results of these study showed that the properties of some SM such as (EFBC) were suitable for the plant growth and development of Andrographis paniculata. In the first glass house experiment, five different combinations of SM were used as growing media which includes; C1 as control = CCD only (1: -), C2 = EFBC + CCD (7:3), C3 = EFBC + CCD (3:7), C4 = CCD + Peat (7:3), C5 = CCD + Peat (3:7) in combination with four nitrogen rates (NR) (0, 30, 60, and 90 kg ha-1) along with and without indigenous microorganism (IMO) application. The growth performance, physiology, biomass production of root and shoot, macronutrient content of leaf tissue and microbial populations in rhizosphere were measured at 30 and 60 day after planting (DAP). At 30 and 60 DAP with application of IMO the soilless media that gave highest growth performance parameter was under C3 media with fertilization of 60 kg N ha-1 compared to control media C1 and other media C2, C4 and C5, plant height (25, 40.8 cm, respectively), number of leaves (121, 132 leaves plant-1) and total leaf area (122.8, 156.7 cm2), dry matter biomass (dry weight of shoot (3.1, 5.1 g), root (0.5, 1.1 g) and total dry biomass (3.6, 6.2 g)) physiological response (photosynthetic rate (9, 10 μmol m-2 s-2), stomatal conductance (410.4, 469.4 mmol m-2 s-1) and transpiration rate (3.9, 4.2 mmol H2O m-2 s-1)) and a decline in all parameter noticed at 90 kg N ha-1. With 90 kg N ha-1 the parameters declined under C3 media in which plant height (19, 37.5 cm, respectively), number of leaves (74.8, 105.8 leaves plant-1) and total leaf area (88, 93.2 cm2), dry matter biomass (dry weight of shoot (1.7, 3.6 g), root (0.3, 0.9 g) and total dry biomass (2, 4.5 g)) physiological response (photosynthetic rate (8.5, 9 μmol m-2 s-2), stomatal conductance (234.8, 363 mmol m-2 s-1) and transpiration rate (2.3, 2.6 mmol H2O m-2 s-1)). While without IMO application, the above mentioned parameters increased with increasing rate of N fertilizer to 90 kg N ha-1 at both planting periods. The combined application of IMO and N fertilizer created positive impact on most of the plant character and total biomass yield of Hempedu bumi grown under C3 media compared to C1 (control). Despite of the fact that EFBC is slow in releasing nutrient but additional of IMO could positively enhance nutrient release from the compost and resulting in highest biomass production of the plant. In second experiment, two soilless media (C1 and C3) from previous studies were chosen base on their effects on the performance of plant growth, physiological parameter and biomass production to further determine their effect on bioactive compound of Andrographis paniculata under WS condition. Media C1 as control and C3 supplied with or without fertilizer. Plant with fertilizer was supplied with 60 kg N ha-1, 15 kg P ha-1, 20 kg K ha-1 and no fertilizer at all was given to the plant without fertilizer. The plants was subjected into three WS levels which include; well watered (WW), moderate water stressed (MS) and severe stressed (SS). The plant received equal amounts of water twice a day for plant establishment and WS treatments were introduced 60 DAP for a period of 21 days. During WS treatments, the leaf relative water content (LRWC) and stomatal conductance (gs) were recorded at 5 days interval and the leaf increments were measured at 3 days interval. Data for biomass production and bioactive compound was determined after 21 days of WS treatment. Results showed that the highest plant biomass production (dry weight of shoot (11.5 and root 1.4 g) was observed from plants grown in C3 media under WW with application of fertilizer. Averaged overall WS treatment with fertilizer application the mean number of leaves and total leaf area (TLA) of plant grown under media C3 exhibited 67% and 31% higher than that of plants grown in C1. While without fertilizer application the number of leaves and total leaf area (TLA) of plant grown in C3 media was 69% and 33% higher than that of plants grown under control media C1. The biochemical compound of the plant was significantly affected by WS condition in which the highest content of andrographolide (0.06 μg mg-1 dry leaf ), proline (3.4 μmole g-1 FW), total phenolic (282.4 ( μg mg-1 extract) and flavonoid (381.8 μg mg-1 extract) content were observed in SS plants grown under media C3 .When averaged across different WS condition, the plant water status and chlorophyll content of plants grown under media C3 were adversely affected by stress condition when the result showed 16% and 57% higher compared to control either with or without fertilizer application, respectively In conclusion, results of this study suggest that the best media proportion was C3 media which consisted of 7: 3 of CCD: EFBC which gave best growth performance as well as biomass production of Andrographis paniculata. Application of IMO as an amendment to soilless media resulted in reducing the used amount of chemical N fertilizer in which the best biomass production was determined when the plant applied with 60 kg N ha-1 and a decline in the biomass was observed with increasing N rate to 90 kg N ha-1. The biochemical content and the secondary metabolite of the plant increased with subjecting the plant to water stress condition. Overall, improvement of SM amended with IMO and maximizing active compound of the herb can be implemented to increase herbal industry in Malaysia.